Introduction of a novel quantitative scoring system for acanthosis nigricans and its validation in a pilot study. Issue 6 (7th November 2020) - Karadag, Ayse Serap; Uzuncakmak, Tugba Kevser; Ozlu, Emin; Takir, Mumtaz; Karadag, Remzi; Kostek, Osman; Simsek, Mehmet; Akdeniz, Necmettin; Wollina, Uwe; Chen, WenChieh
Abstract: Inconsistent data exist regarding the diagnostic value of acanthosis nigricans (AN) or skin tags as clinical markers for obesity or diabetes. In an outpatient department‐based prospective study, we designed a scoring for AN severity (SCANS) to evaluate AN and skin tags, their correlation with obesity or diabetes. Quantification of AN in six anatomic sites, in consideration of the affected skin surface areas, texture changes, number of skin tags, leads to a total severity score between 0 and 46. Among 336 adult patients (aged ≥18 years) with AN, a higher BMI was associated with AN ( r = 0.299, P  < .001), but not with diabetes ( P = .43), as compared with 243 age‐ and sex‐matched controls without AN. Among nondiabetics, AN scores were significantly correlated with waist circumference ( r = 0.131, P = .024) and total cholesterol levels ( r = 0.155, P = .04). Skin tags alone in the absence of AN were not associated with obesity ( P = .333) or diabetes ( P = .164). The total AN scores were positively correlated with the presence of skin tags ( r = 0.132, P  < .001), and the involvement of anterior neck ( r = 0.668, P  < .001) and axilla ( r = 0.793, P  < .001). Knuckles and groins were unaffected in our series. Our results indicate that combination of AN with skin tags can be used as clinical marker for obesity, but not for diabetes. Large‐scale studies on patients of different ethnic background are required to further validate our proposed scoring.